2022
DOI: 10.1007/s00348-022-03381-1
|View full text |Cite
|
Sign up to set email alerts
|

Next generation combined sonic-hotfilm anemometer: wind alignment and automated calibration procedure using deep learning

Abstract: The study of naturally occurring turbulent flows requires ability to collect empirical data down to the fine scales. While hotwire anemometry offers such ability, the open field studies are uncommon due to the cumbersome calibration procedure and operational requirements of hotwire anemometry, e.g., constant ambient properties and steady flow conditions. The combo probe-the combined sonichotfilm anemometer-developed and tested over the last decade has demonstrated its ability to overcome this hurdle. The older… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 20 publications
0
7
0
Order By: Relevance
“…13, varying from 0.3 to 0.7. These values are relatively high but of the same order of magnitude of the values obtained by Kit and Liberzon (2016) and Goldshmid et al (2022) using both traditional and neural network calibration. We expect that in a more favorable setup, such as sonic pointing to the streamwise direction, the sonic velocity would correspond to a better "ground truth" for the velocity fluctuation and the δ i values would be lower.…”
Section: Discussionmentioning
confidence: 55%
See 3 more Smart Citations
“…13, varying from 0.3 to 0.7. These values are relatively high but of the same order of magnitude of the values obtained by Kit and Liberzon (2016) and Goldshmid et al (2022) using both traditional and neural network calibration. We expect that in a more favorable setup, such as sonic pointing to the streamwise direction, the sonic velocity would correspond to a better "ground truth" for the velocity fluctuation and the δ i values would be lower.…”
Section: Discussionmentioning
confidence: 55%
“…This is a cause for concern, since scaling and isotropy are frequently used as measure of the reliability of the data. A more carefully designed field experiment is needed to address some of these questions, ideally including a pre-calibration of the hot-film probe to check all calibration parameters, and a method for reorientation of the sensors in the field (as already present in the combo probe by Goldshmid et al (2022), for example). Future work could also include a validation of the neural network calibration method in the small-scale statistics of the flow.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The authors found that the deblurred images resulted in less PIV velocity error by applying the generator to actual experimental images of a synthetic jet. Authors of [8] presented a study concerning a combined sonic-hotfilm anemometer, and a fully automated in situ calibration procedure implementing DL. The calibration procedure was tested on both the open sea dataset and inside a wind tunnel, it has shown to have the robustness necessary for operation in everchanging open field flow and environmental conditions.…”
Section: Introductionmentioning
confidence: 99%